Self‐Trapped Excitons in 2D SnP2S6 Crystal with Intrinsic Structural Distortion. (12th July 2022) - Zhang, Yue; Wang, Fakun; Feng, Xin; Zhang, Zheng; Liu, Kailang; Xia, Fangfang; Liang, Wenxi; Hu, Xiaozong; Ma, Ying; Li, Huiqiao; Xing, Guichuan; Zhai, Tianyou
Abstract: Exploring and utilizing novel materials with self‐trapped excitons (STEs) is highly desired due to their unique physical properties and multiple optoelectronic applications. Here, a 2D SnP2 S6 crystal is reported with obvious STEs emission caused by distorted [SnS6 ] 8‐ and [P2 S6 ] 4‐ octahedral units and strong electron‐phonon coupling. The STEs feature wide photoluminescence (PL) spectra range from 600 to 850 nm and a large Stokes redshift of ≈0.6 eV. Carrier dynamics measurements including temperature‐dependent PL and transient absorption reveal a large Huang–Rhys factor of ≈18.3 and a self‐trapping process of ≈10 1 –10 3 ps in the 2D SnP2 S6 crystal. Such self‐trapped states enable 2D SnP2 S6 crystal a wide spectral response range and excellent photodetection performance. As a result, high responsivity (22.8 A W ‐1 ) and detectivity (3.98 × 10 10 Jones) are achieved under 365 nm light illumination. These results provide a deep insight into the photophysical process of STEs, which lays the foundation for developing novel STEs‐based materials and optoelectronic devices. Abstract : 2D SnP2 S6 crystal with strong self‐trapped excitons emission induced by distorted [SnS6 ] 8– and [P2 S6 ] 4– octahedral units and strong electron‐phonon coupling is introduced. The features of wide photoluminescence spectrum range, large Stokes shift, ultrafast self‐trapping process, and high photoresponse performance are demonstrated, which enable 2D SnP2 S6 crystal a promising candidate for next‐generation optoelectronic devices.